Natural deep eutectic systems: efficient alternative cryoprotectant agents for the cryopreservation of cells - Jesus, Ana Rita; Paiva, Alexandre; Duarte, Ana Rita (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):298